ESG and corporate performance: The moderating role of government subsidies and mediating effect of analyst coverage in Chinese A-share listed companies - Chuqiao Tang; Xiaolong Guo; Xuan Li (PLoS ONE, 2025)
In recent years, the heightened emphasis on sustainable and high-quality economic development has garnered substantial investor interest in corporate ESG performance, significantly influencing the long-term operational stability of firms. This study, based on data from A-share listed companies from 2015 to 2022, explores the relationship between corporate ESG performance and corporate financial performance. This research employed regression analysis to examine this relationship and found that improved ESG performance significantly enhances financial performance, especially in state-owned enterprises and the manufacturing sector. Additional analysis shows that government subsidies positively influence the relationship between ESG performance and corporate financial performance, suggesting that subsidies amplify the positive effects of ESG initiatives on performance. Mechanism tests suggest that increased analyst coverage is a key pathway through which ESG performance boosts corporate financial performance. These findings underscore the importance of ESG initiatives for companies and provide empirical evidence supporting the role of government subsidies and analyst coverage in amplifying the positive impact of ESG performance on financial outcomes.